Experimental, analytical and numerical investigation to prevent the tow buckling defect during fabric forming. (October 2019) - Salem, M.M.; De Luycker, E.; Fazzini, M.; Ouagne, P.
Abstract: We investigate the causes, kinematic and possible ways to prevent the tow-buckling defect during the complex shape-forming of a dry woven reinforcement. Macro-scale compression leads to wrinkles; we focus on a meso-scale phenomenon generated by a non-uniform axial compression of the tow due to in-plane bending. An experimental study is presented, followed by an efficient method to predict the onset of the tow-buckling defect. This investigation is based on the combination of an experimentally validated analytical approach, with a macro-scale simulation of the forming process for a single fabric layer. A particular focus is given to the resulting tow curvatures that allows us to predict the zones of high tow buckling probability. The relatively simple numerical approach based on Lagrange assumptions does not take into account tow slippage. However, for most cases, where buckles appear before slippage, this approach alleviates the compulsory need for an expensive meso-scale representation.